Early phase interference between low-intensity running and power training in moderately trained females. - Terzis, Gerasimos; Spengos, Kostas; Methenitis, Spyros; Aagaard, Per; Karandreas, Nikos; Gregory Bogdanis (Eur J Appl Physiol, 2016)
PURPOSE: The aim of the study was to investigate the effects of low-intensity running performed immediately after lower-body power-training sessions on power development. METHODS: Twenty young females participated in 6 weeks, 3/week, of either lower body power training (PT) or lower body power training followed by 30 min of low-intensity running (PET) eliciting 60-70 % of maximal heart rate. The following were measured before and after the training period: counter-movement jump, isometric leg press force and rate of force development (RFD), half squat 1-RM, vastus lateralis fiber type composition and cross sectional area, resting intramuscular fiber conduction velocity (MFCV), and heart rate during the modified Bruce treadmill test. RESULTS: Counter-movement jump height and peak power increased after PT (10.7 ± 6.2 and 12.9 ± 18.7 %, p < 0.05) but not after PET (3.4 ± 7.6 and 5.11 ± 10.94 %, p > 0.05). Maximum isometric force, RFD, and half squat 1-RM increased similarly in both groups. Muscle fiber type composition was not altered in either group. Muscle fiber cross sectional area increased only after PT (17.5 ± 17.4, 14.5 ± 10.4, 20.36 ± 11.3 %, in type I, IIA, and IIX fibers, respectively, p < 0.05). Likewise, mean MFCV increased with PT only (before: 4.53 ± 0.38 m s(-1), after: 5.09 ± 0.39 m s(-1), p = 0.027). Submaximal heart rate during the Bruce treadmill test remained unchanged after PT but decreased after PET. CONCLUSION: These results suggest that low-intensity running performed after lower-body power training impairs the exercise-induced adaptation in stretch-shortening cycle jumping performance (vertical jump height, peak power), during the first 6 weeks of training, which may be partially linked to inhibited muscle fiber hypertrophy and muscle fiber conduction velocity.
Keywords: Adaptation, Physiological; Adult; Exercise; Exercise Test; Female; Heart Rate; Humans; Muscle Fibers, Skeletal; Physical Endurance; Quadriceps Muscle; Resistance Training; Running; Young Adult